ANALISIS BUKU AJAR AL-'ARABIYYAH BAINA YADAIK JILID II - Adam Hanip; Ahmad Ahmad; Akhmad Alim (STIQ Amuntai, 2023)
One of the Arabic language textbooks that is widely used in Integrated Islamic High Schools in Indonesia is the book Al-'Arabiyyah Baina Yadaik. This book is organized into four levels and eight volumes. If each volume is completed in one year, it requires ten hours of study in one week, while the study hours at Integrated Islamic High Schools average four to six hours of study in one week. Therefore, from the aspect of completing the Al-'Arabiyyah Baina Yadaik book, it is difficult to achieve this in schools where there are few teaching hours. This study aims to formulate an Arabic language learning module for SMP IT class VIII through analysis of the book Al-'Arabiyyah Baina Yadaik by Abdurrahman Bin Ibrahim Al-Fauzan, Mukhtar Ath-Thahir Husain, and Muhammad Abdul Khaliq Muhammad Fadhl. The type of research used is library research with content analysis techniques. The primary source for this research is the book Al 'Arabiyyah Baina Yadaik by Abdurrahman Bin Ibrahim Al-Fauzan, Mukhtar Ath Thahir Husain, and Muhammad Abdul Khaliq Muhammad Fadhl. The secondary sources are Al'Arabiyyah Li Al-Nasyiin, Silsilat Ta'lim Lughah 'Arabiyah, Al-'Arabiyah li Al-Kibar fi Ta'lim Al-Lughah Al-'Arabiyyah lighairi Al-Nathiqina Biha, and Arabic MTs Kls VIII Ministry of Religion. The purpose of this writing is to analyze the book Al 'Arabiyyah Baina Yadaik Volume II based on four language skills; al-istima>' (listening), al-kala>m (speaking), al-qira>'ah (reading), and al-kita>bah (writing). It is hoped that the results of this analysis will provide an idea of how the model for preparing Al 'Arabiyyah Baina Yadaik is as well as its completeness if applied in schools with few teaching hours.